Employees’ reactance and survival strategies in an underperforming Zimbabwean parastatal - Peter Sibanda; Emmanuel Mavenga; Langtone Maunganidze; Farai Ncube (Academic Journals, 2023)
This research is an analysis of employees’ survival strategies in an under-performing Zimbabwean parastatal. It argues that employees’ survival strategies may evidence failure of an organisation to accommodate changing realities under conditions of distress. The prevailing economic conditions in Zimbabwe may discourage employees from switching jobs even though they are not paid by their employer so that they pursue compensatory actions to survive. This study is based on qualitative research conducted among employees in a Zimbabwean parastatal, which has been struck in perennial performance challenges resulting in its failure to consistently fulfil its obligations to employees as evidenced by delays in salary payments, acute shortages of tools and poor labour relations in general. Employees have resultantly resorted to alternative survival means, such as theft, fabricating leave, moonlighting, including refusal to leave company’s accommodation facilities. They perceive that management is ignorant of their plights, and their interests in formal collective job actions are eroded as they seem to be flogging a dead horse. These employees’ survival strategies are believed to drain the entity’s depreciating resources, with the further milking likely to have ruinous consequences. Most of these strategies are pursued in subtle and unobservable ways to evade immediate management action.